Braiding sweetgrass : indigenous wisdom, scientific knowledge, and the teachings of plants - Kimmerer, Robin Wall (Milkweed Editions, 2020)
"In Braiding Sweetgrass, Robin Wall Kimmerer intertwines two modes of awareness-the analytic and the emotional, the scientific and the cultural-to ultimately reveal a path toward healing the rift that grows between people and nature. This special edition includes a new introduction"--